Memahami Mazmur 23:5a dari Sudut Pandang Eskatologi Pentakosta Klasik: Understanding Psalm 23:5a from a Classical Pentecostal Eschatological View - Silwanus Gabriel (Sekolah Tinggi Teologi Satyabhakti, Malang)
Psalm 23 is one of the psalms of the figurative imaginary of God's existence as a good shepherd. The portrayal of God's existence as a good shepherd brings happiness or blessing to the psalmist. When searching the six verses carefully then verse 5a implies the 'concept of eschatological blessing' for the psalmist who acknowledges and believes in the nurturing of God in his life. The eschatological point of view of Psalm 23: 5a is evident from his statement that